Pengaruh Motivasi dan Budaya Kerja Terhadap Kinerja Pegawai Negeri Sipil Di Pusat Kesenjataan Kavaleri (Pussenkav) Tni Angkatan Darat - Andre Ramu Andika Purbowo; Adhy Firdaus; Muhammad Ramdhan (Jurnal Ilmiah Ekonomi Manajemen & Bisnis, 2023)
This research aims to examine the influence of motivation and work culture on the performance of civil servants at the Army Cavalry Center (Pussenkav) of the Indonesian National Army. The research adopts a descriptive quantitative approach. The population consists of 77 individuals, and the sampling technique employed is saturation sampling, resulting in a total of 77 respondents. Multiple regression analysis is used for data analysis. The research findings indicate that: (1) There is a significant positive influence of motivation on the performance of civil servants at the Army Cavalry Center (Pussenkav) of the Indonesian National Army, with a calculated t-value of 7.047, exceeding the critical t-value of 1.993. The probability value (significance) is 0.000, which is below 0.05. (2) There is a significant positive influence of work culture on the performance of civil servants at the Army Cavalry Center (Pussenkav) of the Indonesian National Army, with a calculated t-value of 4.812, exceeding the critical t-value of 1.993. The probability value (significance) is 0.000, which is below 0.05. (3) There is a significant positive influence of motivation and work culture together on the performance of civil servants at the Army Cavalry Center (Pussenkav) of the Indonesian National Army, with a calculated F-value of 33.145, exceeding the critical F-value of 3.12. The probability value (significance) is 0.000, which is below 0.05